Development and Learning in the Context of Social Interactions: L. Vygotsky vs J. Piaget - Rubtsov, V.V. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2024)
The article is devoted to the problem of contemporary didactics, touching upon the issue of the structure, transmission and acquisition of knowledge.The focus is on understanding the correlation between the content of knowledge and the way it is translated (transmitted) from one person to another, from an adult to a child. We analyze the initial, joint-distributed form of activity that is specific for efficient teaching of children. Статья посвящена проблеме современной дидактики, затрагивающей вопрос строения, передачи и приобретения знания. Основное внимание направлено на то, чтобы понять, в каком соотношении находятся содержание знания и способ его трансляции (передачи) от одного к другому, от взрослого к ребенку. Обсуждается исходная, совместно-распределенная форма деятельности, специфической для эффектного обучения детей.